2014
DOI: 10.7235/hort.2014.13059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Elevated Temperature and Carbon Dioxide on Vine Growth and Fruit Quality of ‘Campbell Early’ Grapevines (Vitis labruscana)

Abstract: The effects of elevated temperature and CO2 concentration on vine growth and characteristics of fruits of three-year-old 'Campbell Early' grapevine were investigated. The treatment groups consisted of a control group (ambient temperature and 390 µL・L -1 CO2), an elevated temperature group (ambient temperature + 4.0°C and 390 µL・L -1 CO2), an elevated CO2 group (ambient temperature and 700 µL・L -1 CO2), and an elevated CO2/temperature group (ambient temperature + 4.0°C and 700 µL・L -1 CO2). The average shoot le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
0
0
1
Order By: Relevance
“…Kimball et al (2002) reported that the partial pressure of CO 2 in plants increases with an increase in the atmospheric CO 2 concentration, which facilitates the diffusion of CO 2 from the atmosphere to the photosynthetic organs, thereby increasing the photosynthetic rate. This CO 2 fertilization effect can be observed in forest trees such as Liriodendron tulipifera L. (Lee et al, 2013), Quercus serrata Murray, and Abies koreana E. H. Wilson (Song et al, 2020) and in fruit trees such as Prunus persica (Lee et al, 2021b) and Vitis vinifera (Son et al, 2014).…”
Section: Photosynthesis Responsementioning
confidence: 94%
“…Kimball et al (2002) reported that the partial pressure of CO 2 in plants increases with an increase in the atmospheric CO 2 concentration, which facilitates the diffusion of CO 2 from the atmosphere to the photosynthetic organs, thereby increasing the photosynthetic rate. This CO 2 fertilization effect can be observed in forest trees such as Liriodendron tulipifera L. (Lee et al, 2013), Quercus serrata Murray, and Abies koreana E. H. Wilson (Song et al, 2020) and in fruit trees such as Prunus persica (Lee et al, 2021b) and Vitis vinifera (Son et al, 2014).…”
Section: Photosynthesis Responsementioning
confidence: 94%
“…Grapes are consumed as fresh fruit as well as used for making wines, juices, grape jam, and Differential Expression of Genes in Response to Temperature Conditions Selected by Transcriptome Analysis of Grapevine Leaves grape seed oil (Park et al, 2010;Salazar-Parra et al, 2012). Recently, rapid climate change has resulted in serious issues such as decreased production and deterioration in quality (Szenteleki et al, 2012;Son et al, 2014). Grapevine genes reveal a different expression pattern in response to high temperatures (Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…지구온난화에 따른 기후변화는 원예작물의 생육기 온도변화를 야기하여 생물계절의 변화, 생산량과 과실 품질 등에 영향을 미치며, 특히 영년생 작물인 과수에서는 수체 생육이 불충실하게 누적되면서 과피의 착색이나 당 함량 등이 저하될 가능성이 제기되고 있다 (Florides and Christodoulides, 2009;Son et al, 2014;Sun et al, 2012). 일본에서는 기후변화에 따른 품목별 대 책을 수립하여 농가에서 실제 활용할 수 있는 기술을 개발하고 있으며, 감귤의 착색기 고온에 의한 착색 불량 및 부피과 발생에 따른 피해를 최소화하기 위한 연구를 수행하고 있다 (Kim and Moon, 2012)…”
unclassified